INTERVENSI INFRARED DAN MUSCLE ENERGY TECHNIQUE SAMA BAIK DENGAN INFRARED DAN PASSIVE STRETCHING DALAM MENURUNKAN NYERI FUNGSIONAL PADA KONDISI LOW BACK PAIN MYOGENIC - Ni Putu Oktaryani Darma Ayu; Ni Luh Nopi Andayani; Susy Purnawati (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT The objective of the study was to find out which one is better between the interventions infrared and muscle energy technique within interventions infrared and passive stretching through the degradation of functional painful of low back pain myogenic condition. The research design that was an experimental research which was designed with pre-test and post-test group design. The sample of the study were 20 persons divided into two groups. Group 1 was given an intervention of infrared and muscle energy technique. Group 2 was given an intervention of infrared and passive stretching. Test Results hypothesis by paired sample t-test showed for group 1 was obtained a result which was p=0,000 with the vary average 4,595±3,658. For group 2 was obtained a result which was p=0,000 with the vary average 5,770±4,332. The result of the study showed a degradation pain which had a significantly in each group. For the average test, the vary between the group 1 and group 2 which used independent sample t-test were found p=0,621 (p>0,05). Based on the results of statistical tests, intervention of infrared and muscle energy technique as well as infrared and passive stretching through degradation of functional painful of low back pain myogenic condition. Keywords: Low back pain, low back pain myogenic, infrared, muscle energy technique, passive stretching, ODI.